MONDE SIFUNISO’S NIGHT THOUGHTS: A FORAY INTO THE CRISIS OF THE STATE IN POSTCOLONIAL AFRICA - KRA Koffi Jérôme & Alama OUATTARA (Ziglôbitha)
Abstract: While the silence of the female voice has long characterised the African literary field, the impact of this one has very often been associated with the gender issue, with the denunciation of the patriarchal system as a point of emphasis. However, beyond gender discourse, the political situation of African states also inspired African authors. Monde Sifuniso, for example, in Night Thoughts, looks at the functioning of the state in postcolonial African society. This study aims to provide a postcolonial and psychoanalytic interpretation of Night Thoughts, analysing the crises that undermine the Barotseland state as depicted by M. Sifuniso. Her narrative portrays a society grappling with disillusionment and trauma due to authoritarianism and mismanagement of public resources. Keywords: Authoritarianism, Monde Sifuniso, Night Thoughts, Political crisis, Trauma